PENGARUH ORIENTASI PASAR TERHADAP KINERJA EKSPOR SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
International trade theories are merely explaining several private business units. Therefore, the development of international trade theories has emerged. This concept developed by focusing on consumer, competitor, influence of exogenous market, and coordination mechanism. West Sumatra is a province that depends on primary export commodities. The West Sumatra export value tends to decreased year by year. This research conducted by using primary data which is collected from exporter in West Sumatra as source of data. The research use 16 variables which are represent consumer, competitor, influence of exogenous market, and coordination mechanism. The research shows that market orientation has significant influence to West Sumatra export performance.